2016
DOI: 10.1177/1359105314565826
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception in Polish patients with chronic diseases: Psychometric properties of the Brief Illness Perception Questionnaire

Abstract: The study evaluates the psychometric properties of a Polish translation of the Brief Illness Perception Questionnaire. A total of 276 patients with chronic conditions (58.7% women) completed the Brief Illness Perception Questionnaire and the Hospital Anxiety and Depression Scale. The internal consistency of the Polish Brief Illness Perception Questionnaire measured with Cronbach's alpha was satisfactory (α = 0.74). Structural validity was demonstrated by significant inter-correlations between the Brief Illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 36 publications
6
27
0
Order By: Relevance
“…39 As expected, our study revealed that anxiety levels and depression were significantly related to perceived lower personal controllability and more burdensome consequences and emotional representation. Similar results were noted by Nowicka-Sauer et al 40 According to the IPQ-R, the higher the test score, the more threatening the illness perception. Significant positive correlations between IPQ-R scores and depression and anxiety were in accordance with this relation.…”
Section: Discussionsupporting
confidence: 89%
“…39 As expected, our study revealed that anxiety levels and depression were significantly related to perceived lower personal controllability and more burdensome consequences and emotional representation. Similar results were noted by Nowicka-Sauer et al 40 According to the IPQ-R, the higher the test score, the more threatening the illness perception. Significant positive correlations between IPQ-R scores and depression and anxiety were in accordance with this relation.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, exposing patients to the belief of low treatment controllability together with the opinion of low patient personal control may deprive patients of hope and decrease their real control over the disease. Considering the previously observed negative correlations between low controllability and depression or anxiety, it may also lead to an increase in patients' distress [13,14]. On the contrary, strong beliefs about treatment controllability as well as personal control would promote hope, cooperation and compliance [6,12].…”
Section: Discussionmentioning
confidence: 92%
“…The Brief Illness Perception Questionnaire (B-IPQ) was used to asses five dimensions of illness perception (consequences, identity, timeline, control personal and treatment, understanding and emotional response) [16]. Recently, the reliability of the Polish version of B-IPQ was proved in a numerous group of patients including those with SLE [14]. In the students' group, a slightly modified version of B-IPQ was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the cronbach α coefficient was 0.76. illness perception was assessed using the Brief illness Perception Questionnaire (B-iPQ) [11]. the cronbach α coefficient of the Polish version of B-iPQ, established in our previous study among patients with chronic conditions, was 0.74 [12]. the Hospital anxiety and depression Scale (HadS) contains 7 questions assessing anxiety and an additional 7 assessing depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%